Sweetpotato crop improvement in sub-Saharan Africa and future challenges - Kapinga, R.; Zhang, D.; Lemaga, B.; Andrade, M.I.; Mwanga, Robert O.M.; Laurie, S.; Ndoho, P.; Kanju, E. (International Society of Tropical Root Crops, 2007)
In sub-Saharan Africa region, most sweetpotato are produced from diverse landraces that have constant turnover. The preference for high dry matter is between 28 to 35%. CIP breeding strategy for the past 15 years has been to collect, characterize, and conserve farmers' varieties; evaluate and distribute the best performers regionally. It has also emphasised population development through crosses and systematic screening with partners using participatory methods. Key stages of breeding programme incorporate breeders. ICM specialists, postharvest technologists, social scientists, consumers and farmers. To day several varieties have been released officially by the national programmes and of recent orange-fleshed sweetpotato (OFSP) varieties have been given emphasis in almost all the countries in ASARECA and SADC regions. Varieties such as SPK004, Mogamba, Zapallo (for children), Salyboro, Pumpkin, SPK013, and Kemb10 (yellow-fleshed), Zapallo, Japon Tresminiso, Tainung 64, Resisto and Kandee have gained popularity. Multiplication and distribution of planting materials have continued by individual farmers and community based organizations. In Western Kenya, about 30 million cuttings of mainly OFSP varieties have been distributed to farmers from KARI stations and local CBO's/NGO's. In the Lake Zone of Tanzania, about 6 million of three newly released varieties (SP93/23, SP93/2, and SP93/34) together with local varieties Sinia and Simama (SPN/O); and in Uganda farmers with BUCADEF and SOCADIDO have distributed about 10 million cuttings of the newly NARO released varieties (NASPOTs 1-5) to farmers. Improved varieties distributed in East African region, have covered over 360 hectares of fields. In Mozambique an estimated 154 ha have been planted with improved varieties. Over 347,000 households in Mozambique have receive at least 200 vines of OFSP sweet potato and projections are that over one million households will have received planting material by 2004.